Analysis of Project Manager Leadership Competencies in Managing Traditional, Contemporary, Eco-Friendly, and Carnival Collaborations at Polbeng Expo Chapter II - Clara Tri Andini; Wan Junita Raflah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Effective event management plays an essential role in ensuring the successful implementation of large-scale educational events. This study aims to analyze the management aspects applied in presenting Traditional, Contemporary, Eco-Friendly, and Carnival fashion collaborations at Polbeng Expo Chapter II. The research focuses on the implementation of leadership, planning, coordination, communication, and decision-making by the Project Manager throughout the event management process. A descriptive qualitative approach was employed using purposive sampling to select committee members who were directly involved in organizing the event. Data were collected through semi-structured interviews using the Behavioural Event Interview (BEI) approach and supported by direct observation. Data analysis referred to the AKEPT leadership competency framework to evaluate managerial competencies demonstrated during project implementation. The findings indicate that effective planning, cross-functional coordination, adaptive leadership, and timely decision-making significantly contributed to the successful implementation of the fashion show. The Project Manager demonstrated competencies at the Managing Function and Integrating Diverse Functions levels, indicating effective leadership in coordinating multiple divisions and managing project execution. The study concludes that strong management practices enhance collaboration, improve team performance, and contribute to achieving event objectives successfully.